(untitled) (Human Factors in Design, 2025)
The transportation and handling of loads often require operators to exert physical force to reach their final destination. Therefore, it is crucial for fleet managers to adequately manage the risks involved in these activities. The present study aims to perform an ergonomic analysis of the physical workload using the Rapid Entire Body Assessment (REBA) method and to demonstrate that this method can be effective in the decision-making process of managers regarding ergonomic issues. The method provides rapid results on the impacts of physical workload on the worker’s body, making it a valuable tool for managers to assess and address ergonomic risks. The results showed that the method was useful for the proposed situation and that operators perform 50% of their activities under a very high ergonomic risk.